Experiencias de aprendizaje en el desarrollo cognitivo de los niños de 2 a 3 años del Centro de desarrollo infantil ciudad Alegría ubicado en la ciudad de Loja, periodo 2019 – 2020 - León Torres, Guissella Vanessa (2021)
This investigation’s main goal was to analyze the importance of the learning experiences in the cognitive development of 2-to-3-year olds. This research was a non-experimental study; which allowed to observe children in their regular environment. Furthermore, this study combined a quantitative method, which recollected data and a qualitative method which allowed to take into account the main features from children and teachers. In order to develop this research, the descriptive, analytic – synthetic and inductive- deductive methods were applied. The instruments that were used were surveys, observation and Bailey’s child development scale. This research was part of the Early Education Career’s investigation project, which diagnosed 11 Child Development Centers in Loja. This investigation was applied on one Early Education Center which works with 36 children, the sample was 11 children and 3 teachers. The most relevant outcomes identified that 100% of the kids had a low cognitive development result. Therefore, it could be stated that it is necessary to apply the alternative proposal based on learning experiences in order to improve the children’s cognitive development, which is named “While playing and experimenting, I keep on developing”, which will be delivered for its further application.